Nilai-Nilai Pendidikan Anak Usia Dini dalam Al-Qur’an (Studi Surah Luqman Ayat 12-19) Menurut Tafsir Ibnu Katsir - Nashiruddin, Ahmad; Zahrok, Fatimatuh; Farouq, Umar (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Pesantren Mathali'ul Falah Pati, 2023)
The author is interested in focusing his research on surah Luqman verses 12-19 because this verse has the closest meaning to early childhood education. This research uses library research with efforts to search for literature references related to the subject matter discussed descriptively, namely research that collects materials, books, supporting literature. The data analysis technique used in this study is content analysis by analyzing the meaning contained in the verses of the Qur'an related to early childhood according to surah al-Luqman verses 12-19 according to the tafsir of Ibn Kathir. The results showed that the educational value that needs to be instilled from surah al-Luqman verses 12-19 includes aqidah education, shari'ah education, and moral education.